Assessment of Color Parameters on Maxillary Right Central Incisors Using Spectrophotometer and RAW Mobile Photos in Different Light Conditions - Mirko Soldo; Davor Illeš; Robert Ćelić; Dubravka Knezović Zlatarić (University of Zagreb. School of Dental Medicine, 2020)
Objectives: The aim of the study was to compare three color parameters assessed on the maxillary right central incisors using a spectrophotometer as the gold standard, along with RAW mobile calibrated and non-calibrated photos in different light conditions. Materials and methods: A total of 30 dental students participated in the study. CIE L*a*b* values were measured in the middle third of each maxillary right central incisor spectrophotometrically and digitally on RAW mobile dental photos using different light conditions (F-frontal light; L-lateral light; D-lateral light with diffusers; P- polarizing filter on frontal light; H-hybrid filter as combination of frontal light with polarizing filter and lateral lights with diffusers) with LEDs (light emitting diode) in full power, and with gray card calibration. The obtained results were compared. Results: Mean a* and b* values on calibrated, as well as mean L* values on non-calibrated RAW mobile photos did not significantly differ in different light conditions (P>0.05). CIE L*a*b* values on non-calibrated polarizing RAW mobile photos completely matched the same values obtained using a spectrophotometer on the subject's maxillary right central incisor (P>0.05). Conclusions: Different light conditions and measuring procedures affected CIE L*a*b* values on RAW mobile photos in this study. Within the limitations, non-calibrated RAW mobile photos using a lightening device with polarizing filters on frontal LED light in standardized conditions can be a useful tool for digital dental shade determination.